Rapid Outgassing of Hydrophilic TiO2 Electrodes Achieves Long-Term Stability of Anion Exchange Membrane Water Electrolyzers - Shaik, Shajahan; Kim, Jeonghyeon; Kabiraz, Mrinal Kanti; Aziz, Faraz; Park, Joon Yong; Anne, Bhargavi Rani; Li, Mengfan; Huang, Hongwen; Nam, Ki Min; Jo, Daeseong; Choi, Sang‑Il (Nano-Micro Letters, 2025)
The state-of-the-art anion-exchange membrane water electrolyzers (AEMWEs) require highly stable electrodes for prolonged operation. The stability of the electrode is closely linked to the effective evacuation of H2 or O2 gas generated from electrode surface during the electrolysis. In this study, we prepared a super-hydrophilic electrode by depositing porous nickel–iron nanoparticles on annealed TiO2 nanotubes (NiFe/ATNT) for rapid outgassing of such nonpolar gases. The super-hydrophilic NiFe/ATNT electrode exhibited an overpotential of 235 mV at 10 mA cm−2 for oxygen evolution reaction in 1.0 M KOH solution, and was utilized as the anode in the AEMWE to achieve a current density of 1.67 A cm−2 at 1.80 V. In addition, the AEMWE with NiFe/ATNT electrode, which enables effective outgassing, showed record stability for 1500 h at 0.50 A cm−2 under harsh temperature conditions of 80 ± 3 °C. Highlights: 1 A super-hydrophilic electrode was successfully developed by depositing porous NiFe nanoparticles onto annealed TiO2 nanotubes (NiFe/ATNT), facilitating rapid outgassing of nonpolar gases. 2 The NiFe/ATNT electrode demonstrated an overpotential of 235 mV at 10 mA cm−2 for the oxygen evolution reaction in 1.0 M KOH and served as the anode in the anion exchange membrane water electrolyzer (AEMWE), achieving a current density of 1.67 A cm−2 at 1.80 V. 3 The AEMWE utilizing the NiFe/ATNT electrode exhibited remarkable stability, maintaining operation for 1500 h at 0.50 A cm−2 under challenging thermal conditions of 80 ± 3 °C.